Implementasi Asesmen Kinerja Berpikir Kritis Berbasis ESD Pada Pembelajaran Daring di Sekolah Dasar - Umi Amellya Pangestika; Ghullam Hamdu (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to analyze the implementation of ESD-based critical thinking performance assessment in the online learning process and to find out the difficulties that occur when using critical thinking performance assessment instruments during the online learning process. The research was conducted in elementary schools. This research uses descriptive qualitative research method. The subjects used in this study were high school elementary school teachers. Data collection techniques used in this study were interviews and documentation studies. The results of the study indicate that teachers have difficulty in evaluating critical thinking performance in Education for Sustinable Development (ESD) based learning which contains three perspectives, namely environmental, social and economic which is carried out online. Teachers cannot use performance appraisal instruments optimally due to several reasons such as the lack of supporting facilities and infrastructure for the implementation of the online learning process and teachers also cannot see directly the work of students' assignments.